STRATEGI PEMBERDAYAAN INDUSTRI KECIL DAN KERAJINAN MELALUI PENGEMBANGAN PEMASARAN DAN PERMODALAN DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA - Prasetyo, P. Eko (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
The strategies for developing of small-scale enterprise are relying on data come from secondary sources of information especially from several research and studies reports. Small businesses are an economic activity dominating more than 95% of Yogyakarta s economic structure. This sector has both economic and social politic strategic role. The economic function of this sector, among others, to provide merchandises and service for consumers from low to middle level of purchasing power; it contributes more than a half of economic growth and is contributive to the countrys foreign exchange income. Socio politically, the function of this sector is also crucial, especially in labour absorption and in the poverty alleviation efforts. Apart from the above, small business development is basic need for Yogyakarta, which practices a specific economic system, namely peoples economy. Indonesias economic system prioritizes peoples economic interest, namely that which involves public interests.